Continuous hypergravity alters the cytoplasmic elasticity of MC3T3-E1 osteoblasts via actin filaments. (27th April 2018) - Zhou, Shuai; Yang, Xueyi; Hu, Jiliang; Mo, Chi; Cao, Yanping; Yang, Chun
Abstract: Osteoblasts are sensitive to altered gravity conditions, displaying changes in RNA and protein expression, proliferation, and differentiation; however, the effect of hypergravity on the mechanical properties of osteoblasts remains unclear. In this study, atomic force microscopy (AFM) was used to evaluate the effect of hypergravity on the elasticity of osteoblasts. We demonstrate that a continuous hypergravitational environment increased the elasticity of the cytoplasm, but not the nuclei zone, of MC3T3-E1 osteoblasts. Actin filaments, but not microtubules, dominated in the increased elasticity. These findings provide new insights on cellular gravity-sensing mechanisms.